Impact of DNA double-strand breaks on pancreaticobiliary maljunction carcinogenesis - Yasuhiro Kuraishi; Takeshi Uehara; Takashi Muraki; Mai Iwaya; Yasuhiro Kinugawa; Tomoyuki Nakajima; Takayuki Watanabe; Yusuke Miyagawa; Takeji Umemura (BMC, 2021)
Abstract Background Pancreaticobiliary maljunction (PBM) is a condition characterized by chronic inflammation due to refluxed pancreatic juice into the biliary tract that is associated with an elevated risk of biliary tract cancer. DNA double-strand breaks (DSBs) are considered the most serious form of DNA damage. DSBs are provoked by inflammatory cell damage and are recognized as an important oncogenic event in several cancers. This study used γ-H2AX, an established marker of DSB formation, to evaluate the impact of DNA damage on carcinogenesis in PBM. Methods We investigated γ-H2AX expression immunohistochemically in gallbladder epithelium samples obtained from 71 PBM cases and 19 control cases. Results Fourteen PBM cases with gallbladder adenocarcinoma were evaluated at non-neoplastic regions. A wide range of nuclear γ-H2AX staining was detected in all PBM and control specimens. γ-H2AX expression was significantly higher in PBM cases versus controls (median γ-H2AX-positive proportion: 14.4 % vs. 4.4 %, p = 0.001). Among the PBM cases, γ-H2AX expression was significantly higher in patients with carcinoma than in those without (median γ-H2AX-positive proportion: 21.4 % vs. 11.0 %, p = 0.031). Conclusions DSBs occurred significantly more abundantly in the PBM gallbladder mucosa, especially in the context of cancer, indicating an involvement in PBM-related carcinogenesis.